WHAMM is essential for spindle formation and spindle actin polymerization in maturing mouse oocytes. Issue 2 (17th January 2021) - Jo, Yu-Jin; Kwon, Jeongwoo; Jin, Zhe-Long; Namgoong, Suk; Kwon, Taeho; Yoon, Seung-Bin; Lee, Dong-Ho; Kim, Ji-Su; Kim, Nam-Hyung
ABSTRACT: WHAMM (WAS Protein Homolog Associated with Actin, Golgi Membranes, and Microtubules) is involved in Golgi membrane association, microtubule binding, and actin nucleation as a nucleation-promoting factor, which activates the actin-related protein 2/3 complex (the Arp2/3 complex). However, the role of WHAMM in mammalian oocyte maturation is poorly understood. The presence of WHAMM mRNA and protein during all stages of mouse oocyte maturation has been verified. It is mainly co-localized with the actin cage permeating the spindle during mouse oocyte maturation. Through the knockdown of WHAMM, we confirmed that it regulates spindle formation and affects the localization of the microtubule-organizing center (MTOC) during the early stages of spindle formation. Moreover, depletion of WHAMM impaired the formation of the spindle actin and chromosome alignment, which might be the cause of chromosomal aneuploidy and abnormal, asymmetric division. Treatment with brefeldin A (BFA), an inhibitor of vesicle transport from the endoplasmic reticulum (ER) to the Golgi apparatus, induced abnormal and dispersed localization of WHAMM. Taken together, these findings show that WHAMM is an essential component of the actin cytoskeleton machinery and plays a crucial role in oocyte maturation, presumably by controlling the formation of spindles with normal length by activating the formation of the spindle actin via the Arp2/3 complex.